2000
DOI: 10.1038/35018098
|View full text |Cite
|
Sign up to set email alerts
|

A one-hit model of cell death in inherited neuronal degenerations

Abstract: In genetic disorders associated with premature neuronal death, symptoms may not appear for years or decades. This delay in clinical onset is often assumed to reflect the occurrence of age-dependent cumulative damage. For example, it has been suggested that oxidative stress disrupts metabolism in neurological degenerative disorders by the cumulative damage of essential macromolecules. A prediction of the cumulative damage hypothesis is that the probability of cell death will increase over time. Here we show in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
243
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(276 citation statements)
references
References 22 publications
29
243
3
1
Order By: Relevance
“…Therefore, we conclude that the exponential model is sufficient to describe the long-term course of cone ERG amplitude decline in patients with typical retinitis pigmentosa. These observations in patients with retinitis pigmentosa are consistent with a previous study in animals with hereditary photoreceptor degeneration (Clarke, et al, 2000) that found that an exponential model described the rate of loss of retinal cells and ERG amplitude as a function of aging, supporting the conclusion that the risk of individual cell death in these genetic diseases is random and remains constant with increasing age.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, we conclude that the exponential model is sufficient to describe the long-term course of cone ERG amplitude decline in patients with typical retinitis pigmentosa. These observations in patients with retinitis pigmentosa are consistent with a previous study in animals with hereditary photoreceptor degeneration (Clarke, et al, 2000) that found that an exponential model described the rate of loss of retinal cells and ERG amplitude as a function of aging, supporting the conclusion that the risk of individual cell death in these genetic diseases is random and remains constant with increasing age.…”
Section: Nih-pa Author Manuscriptsupporting
confidence: 91%
“…Therefore, we conclude that the exponential model is sufficient to describe the long-term course of cone ERG amplitude decline in patients with typical retinitis pigmentosa. These observations in patients with retinitis pigmentosa are consistent with a previous study in animals with hereditary photoreceptor degeneration (Clarke, et al, 2000) that found that an exponential model described the rate of loss of retinal cells and ERG amplitude as a function of aging, supporting the conclusion that the risk of individual cell death in these genetic diseases is random and remains constant with increasing age.In this population, subgroup analyses by genetic type revealed that the average annual rates of decline of remaining cone ERG amplitudes for dominant, recessive, X-linked, and isolate cases are fairly comparable to each other, compatible with the idea that one rate of decline can be used in clinical practice to describe the average long-term course of disease in this condition (for dominant disease see Berson et al, 2002; for X-linked disease see Sandberg et al, 2007, in press). The clinical finding that X-linked patients usually become blind before dominant cases can be explained by the fact that children with X-linked disease at a given age usually have less cone function than children with dominant disease even though their cone ERGs are declining at about the same rate.…”
supporting
confidence: 91%
“…The mutations we examined cause retinal degeneration either as a primary disorder of rod photoreceptors (RHO, rhodopsin) or as a disorder of both rod and cone photoreceptors (RPGR, retinitis pigmentosa GTPase regulator; RDS (also called PRPH2), retinal degeneration slow or peripherin 2; TULP1, tubby-like protein 1; ATXN7 (also called SCA7), ataxin 7 or spinocerebellar ataxia 7). Most cause rates of degeneration that are consistent with a one-hit exponential decay model of cell death 5,6,9 .…”
Section: Measuring Rates Of Degenerationsupporting
confidence: 55%
“…Caspase-independent cell death also occurs, although the precise mechanisms are less well understood and evidence that this occurs in inherited neurodegenerations is sparse. In these disorders, cell death occurs with a probability that is constant through part or all of the adult lifespan, consistent with a steady-state (one-hit or exponential kinetics) rather than a cumulative damage model 5,6 . The retina is a particularly well understood model of neurodegeneration.…”
mentioning
confidence: 65%
See 1 more Smart Citation